Delayed iatrogenic diaphragmatic hernia after thoracoscopic lobectomy - Pan, Sai-Bo (J Thorac Dis, 2016)
Postoperative iatrogenic diaphragmatic hernia after thoracoscopic lobectomy is extremely rare. We present a 55-year-old female patient who developed an iatrogenic diaphragmatic hernia with gastric perforation several months after VATS (video-assisted thoracic surgery) left upper lobectomy with systematic lymphadenectomy. During the readmission, urgent laparotomy was performed. Intraoperatively, the choledochoscopy was introduced into left thoracic cavity through the diaphragmatic defect for dissecting the secondary inflammatory adhesions and achieving satisfactory hemostasis. It appears to be an efficient and feasible approach for the patients who have been diagnosed as delayed diaphragmatic hernia concomitant with remarkable intra-abdominal findings and have a history of thoracic surgery. We consider that delayed-onset diaphragmatic hernia should be suspected in patients complaining of nausea or vomiting after VATS procedure, although it is very rare.